2003
DOI: 10.1002/hup.515
|View full text |Cite
|
Sign up to set email alerts
|

Stem‐completion tasks (indirect, direct inclusion and exclusion) are differently affected by equipotent doses of lorazepam and flunitrazepam

Abstract: This study was designed to explore the effects on performance in stem-completion tasks of two benzodiazepines (BZ) in equipotent doses: lorazepam, a drug that atypically disrupts perceptual priming, and flunitrazepam, a compound with standard BZ effects. The study followed a placebo-controlled, double-blind, parallel-group design. Thirty-six young and healthy subjects carried out three completion tasks at theoretical peak-plasma concentrations of drugs: (a) indirect tasks, in which the subjects were instructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
2
10
1
Order By: Relevance
“…Results in the control tasks (CT, DSST, VAS and Prose Recall) revealed lower performance of Flu1.0 and Flu1.3 in comparison to placebo, indicating that the doses used in the present study were high enough to corroborate previous findings of cognitive effects of BDZ (psychomotor, attentional, subjective and amnesic) (Buffett-Jerrott and Stewart, 2002;Curran, 2000;Pompéia et al, 2000Pompéia et al, , 2003. Memory impairment was evident in free recall of words and prose even though normal forgetting rate was observed in recall of prose after flunitrazepam ingestion.…”
Section: Discussionsupporting
confidence: 92%
“…Results in the control tasks (CT, DSST, VAS and Prose Recall) revealed lower performance of Flu1.0 and Flu1.3 in comparison to placebo, indicating that the doses used in the present study were high enough to corroborate previous findings of cognitive effects of BDZ (psychomotor, attentional, subjective and amnesic) (Buffett-Jerrott and Stewart, 2002;Curran, 2000;Pompéia et al, 2000Pompéia et al, , 2003. Memory impairment was evident in free recall of words and prose even though normal forgetting rate was observed in recall of prose after flunitrazepam ingestion.…”
Section: Discussionsupporting
confidence: 92%
“…The use of a more refined paradigm to investigate memory impairment, the PDP (Jacoby 1991), also showed that 10 mg zolpidem affects C, confirming that this drug impairs episodic memory as observed through the application of this same paradigm to data from BZ-treated subjects (Vidailhet et al 1996;PompØia et al 2003a).…”
Section: Discussionsupporting
confidence: 59%
“…The medications used for anesthesia have different effects on memory 18,[20][21][22] . In our study, patients were not premedicated, so that the results would not be affected.…”
Section: Discussionmentioning
confidence: 99%